2016
DOI: 10.1177/1359105315587138
|View full text |Cite
|
Sign up to set email alerts
|

Who does not get screened? A simple model of the complex relationships in mammogram non-attendance

Abstract: With increasing mammogram rates, identifying attributes of non-attending women entails going beyond differences in demographic groups to reveal complex interactions among personality attributes. In this study, we analyzed survey data from 474 women aged 41 years and older using decision trees. By incorporating personality, religiousness, and age, we were able to correctly classify 42.9 percent of non-attenders compared to 4.4 percent with logistic regression analysis. Our findings suggest that incorporating pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 38 publications
0
26
1
2
Order By: Relevance
“…For example, Schwartz [46] showed that increased conscientiousness was marginally significantly associated with mammogram utilization (OR = 0.74, 95% CI: 0.21-2.56). Another study [47] showed that increased conscientiousness was associated with mammogram attendance (OR = 2.13, 95% CI: 1.23-3.69). Similar findings were made by Pandhi et al [45].…”
Section: Conscientiousness and Use Of Cancer Screeningsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Schwartz [46] showed that increased conscientiousness was marginally significantly associated with mammogram utilization (OR = 0.74, 95% CI: 0.21-2.56). Another study [47] showed that increased conscientiousness was associated with mammogram attendance (OR = 2.13, 95% CI: 1.23-3.69). Similar findings were made by Pandhi et al [45].…”
Section: Conscientiousness and Use Of Cancer Screeningsmentioning
confidence: 99%
“…Moreover, no studies were excluded because they used an invalid tool to assess personality or cancer screening. In total, n = 11 studies were included in our final synthesis (total number of observations: n = 338,091) [20,21,[39][40][41][42][43][44][45][46][47]. The quality assessment of included studies is described in Table 2.…”
Section: Overview: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations